TEACHING ENGLISH TO CHILDREN AT MI TAHFIDZ NURUL HUDA JAPURALOR, CIREBON - Umar, Umar (STIT Buntet Pesantren Cirebon, 2022)
Since the implementation of the decentralization policy in education management in 2001, many local governments (PEMDAs) have decided to teach English as a local content (Mulok) at the elementary school level (or even in kindergarten). This local government initiative is problematic because the implementation of this mulok is not accompanied by special efforts to prepare some important aspects such as English teachers to teach in elementary schools and some supporting facilities. This research was conducted within 2 months (from January - February 2022). They were an English teacher at MI Tahfidz Nurul Huda Japuralor and some students of MI Tahfidz Nurul Huda Japuralor. The subjects were selected using Purposive Sampling techniques. This article discusses an overview of teaching English to children in MI Tahfidz Nurul Huda Japuralor, teachers’ perception toward teaching English to Young Learners, and Parents’ persepectives on learning English.